Tobacco abuse and dental problems among sanitation workers of Allahabad city: a cross sectional study - Ansari, Abdul M. M.; Prakash, Shiv; Parveen, Khurshid; Anand, Deepak (International Journal Of Community Medicine And Public Health, 2019)
Background: ‘Sanitary labourers’ are known by different names such as ‘Health Labourers’, ‘Manual Scavengers’ garbage man, trash man etc. They are mainly involved in street cleaning, waste carrying, drainage and toilet cleaning in the cities. Intake of alcohol and tobacco products is prevalent to cope with the inhuman task of cleaning filthy sewage, and as a modality to forget their health problems. The aim of the present cross-sectional study was to find out the association of dental problems with tobacco abuse among the study population. Methods: The study population included 610, 122 from each zone of Allahabad city through “Proportionate stratified random sampling”. The study subjects was interviewed and examined, Dental problems were assessed by taking history, doing a clinical examination, reviewing past medical records. Results: Dental problems were found to be higher in prevalence among “exclusive smokers”, “combined abuser” and “exclusive tobacco” chewers as compared to “non abuser”. Dental caries were found to be higher in prevalence among the entire three abusers group as compared to “non abusers”. Missed teeth were found to higher in prevalence among “combined abuser” and “exclusive tobacco chewers” group as compared to “non abusers”. Enamel erosion was found to be higher among “exclusive tobacco chewers” group as compared to “non abusers”. All these finding were found to be statistically significant. Conclusions: Dental problems were found to be more prevalent among tobacco abusers than non abusers.